Critical role of strain partitioning and deformation twinning on cracking phenomenon occurring during cold rolling of two duplex medium manganese steels. (15th March 2017) - Sun, Binhan; Fazeli, Fateh; Scott, Colin; Yan, Xiaojun; Liu, Zhiwei; Qin, Xiaoyu; Yue, Stephen
Abstract: Two ferrite-austenite duplex medium manganese steels with very similar phase fractions and grain sizes were subjected to cold rolling. The 10Mn steel presented a much better cold rollability compared with the 7Mn steel, which is believed to stem from two critical factors. Firstly, the larger strain partitioning in the 10Mn steel resulted in a less deformation accommodated by the brittle δ-ferrite, which delayed or even inhibited micro-crack formation inside the ferrite phase. Secondly, the deformation twinning activated in the austenite of the 10Mn steel during rolling effectively enhanced the ductility of the austenite-martensite (γ-α′) mixed phase. Graphical abstract: